PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. SUKA FAJAR PEKANBARU - Raja Devi Ramadanita; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to determine the effect of compensation and work environment on employee job satisfaction partially and simultaneously at PT. Suka Fajar Pekanbaru. This study uses questionnaires as a means of collecting data distributed to 69 employees by using the slovin formula. Sampling method in this research using proportional random sampling method. The data from the questionnaire was further processed using descriptive analysis and statistical analysis using SPSS 21.0 by performing validity test, reliability test, simple linear analysis, multiple linear analysis, determination analysis (R²) and hypothesis test with t test (partial) and F ( Simultaneous).The results showed that the results of the first hypothesis testing of compensation on employee job satisfaction is t hitung (10,078) > t tabel (1,996), meaning that compensation variable significant effect on employee job satisfaction. Both work environment on employee job satisfaction is t hitung (8,643) > t tabel (1,996), meaning work environment has a significant effect on employee job satisfaction. The result of F test of compensation and work environment on employee job satisfaction is F hitung (62,814) > F tabel (3,136), meaning that compensation and work environment simultaneously have a significant effect on employee job satisfaction.Keywords: Compensation, Work environment, Employee Job Satisfaction